Peripheral vestibular dysfunction and Horner’s syndrome secondary to extension of chronic exudative otitis externa in a cat - A case report - Jadav, Mayur M.; Joshi, Vivek; Das, Manas; Deepsikha,; Dimri, Umesh (Indian Journal of Veterinary Medicine, 2024)
Otitis media and interna are significant causes of peripheral vestibular disease in cats, often accompanied by Horner's syndrome. This case report presents a 4-month-old male long-haired cat diagnosed with peripheral vestibular disease secondary to extension of exudative otitis externa. Clinically apparent signs were exudation from external ear, circling, ataxia and Horner's syndrome. Treatment included a combination of amoxycillin-potassium clavulanate, prednisolone, neuroprotective agents and antibacterial/antifungal ear drops. The cat showed gradual improvement and completely recovered after two weeks of continual therapy.